2012
DOI: 10.2478/v10201-011-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

The Recent View on the Obstructive Sleep Apnoea Syndrome in Children – Short Résumé

Abstract: A b s t r a c tThe authors present a recent overview of the common clinical manifestations, management, diagnostic criteria and currently accepted treatment approaches of children with obstructive sleep apnoea syndrome (OSAS). Paediatric OSAS has become widely recognized as a frequent disorder and as a major public health problem. Diagnosis of this problem is usually based on physical examination, history and clinical evaluation confirmed by the polysomnography (PSG). PSG is considering as a gold-standard test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Recently it has been reported that delayed diagnosis of this syndrome can lead to serious cardiorespiratory morbidity, metabolic complications, neurobehavioural consequences as well as an increase in insulin resistance, high blood pressure and the development of this syndrome in adulthood. This condition should be diagnosed, managed and treated aggressively with having these new repercussions (1,2,4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been reported that delayed diagnosis of this syndrome can lead to serious cardiorespiratory morbidity, metabolic complications, neurobehavioural consequences as well as an increase in insulin resistance, high blood pressure and the development of this syndrome in adulthood. This condition should be diagnosed, managed and treated aggressively with having these new repercussions (1,2,4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Также связанное с затрудненным дыханием нарушение сна может привести к проблемам с обучением и поведением [9]. Кроме того, нарушение сна, связанное с ГНМ, может приводить к инсулинорезистентности и к артериальной гипертензии в зрелом возрасте [10]. Чрезвычайно важно отметить, что ГНМ может сопровождаться хроническим воспалением миндалин (хроническим тонзиллитом (ХТ)).…”
unclassified